Study of Dicumyl Peroxide in Crosslinking Process of a SBS-Based Pressure Sensitive Adhesive - Salazar-Cruz, Beatriz Adriana; Rivera-Armenta, José Luis; de la Garza, Alejandro Esquivel; Morales-Cepeda, Ana Beatriz; Ramos-Galván, Claudia Esmeralda (Journal of Composites and Biodegradable Polymers, 2018)
The styrene-butadiene-styrene (SBS) is a thermoplastic copolymer commonly used as pressure sensitive adhesive (PSA), due its they are highly flexible and elastics, that produce high cohesive strength that results in physical interactions caused by polystyrene (PS) blocks. However, SBS-based PSA’s restrain their adhesion properties around their glass transition temperature (Tg), so it is necessary to add a crosslinking agent to increase their thermal resistance. Crosslinking is an important process in adhesives formulations, due that the mechanical properties of adhesive improve, but not enough information I published about the kinetic of that process. One of most studied crosslinking agent for adhesive formulations is dicumyl peroxide (DCP), which shows a good combination of physical and chemical properties to adhesive during crosslinking process. This report presents a crosslinking process using DCP as crosslinking agent. The study of kinetic parameters was determined by differential scanning calorimetry (DSC) in isothermal and dynamic conditions, from which the order of the crosslinking process reaction was found to be first order, according to the Kissinger and Ozawa models. The adhesive and cohesive strength was evaluated through the failure criterion between the bonds of the adhesive line using the single lap join method (SLP), showing that the best performance was that of the formulation made from resin Sylvalite RE100L and 0.81phr of DCP.